Laparoscopic morgagni hernia repair using single-site umbilical and full-thickness abdominal wall repair: Technical report of two cases - Martin L van Niekerk (Wolters Kluwer Medknow Publications, 2013)
Single incision laparoscopic surgery is used in many centres for routine cases such as appendisectomy, splenectomy and cholecystectomy. Morgagni hernias are uncommon and account for 1-2% of all congenital diaphragmatic hernia. We report our first laparoscopic repair of two Morgagni hernias, using a single umbilical incision and full-thickness abdominal wall repair with standard straight laparoscopic instruments. Operative time was short and compared favourably with the laparoscopic repair.